Transition of Poverty in Pakistan: Evidence from the Longitudinal Data (The Pakistan Development Review, 2004)
Interest in the dynamics of income and consumption at the household level has increased in the developing countries as measures of living conditions at a point in time are not necessarily a good indicator of its stability over time. For many purposes it is important to adopt a dynamic perspective, distinguishing between extremely, chronically or transitory poor. In Pakistan studies of poverty at a point in time provide very valuable information about its nature, characteristics and distribution. However, given the fluctuations in many dimensions of poverty such as school enrolment, nutritional status and income, these studies are unable to capture the dynamics of this phenomenon, making it impossible to analyse the factors associated with the poverty transition, i.e., movement into and out of poverty.